Overuse noncontact ACL injury in young athletes: Since we can`t completely fix it, why not prevent it? - Nyland, J. (Sports Health: A Multidisciplinary Approach, 2023)
The youth and adolescent athletes of today experience seemingly endless seasons, with minimal recovery, poor nutrition, and high volume performance and skill training that does not consider the need for ligament healing homeostasis. In the Bob Marley song "I Shot the Sheriff," the lyrics state that "reflexes got the better of me and what is to be must be, every day the bucket goes into the well, one day the bottom drops out." In many youth and adolescent athletes, these reflexes represent regular musculoskeletal and cardiopulmonary system or skill training, with little or no consideration for total volume, intensity, or duration. The bottom of the bucket represents the anterior cruciate ligament (ACL), a tissue with a slower extracellular matrix (ECM) and enthesis healing rate. The obsessive sport passion that many youth and adolescent athletes possess negates the likelihood of any voluntary training modifications or competition scheduling in favor of the recovery needed to avoid overuse.